EXPERIENCE REPORT: TEACHING RESIDENCY IN REMOTE TEACHING DURING THE PANDEMIC - Yara de Araujo Nunes, Estella; Edjane Marcelino Magalhães Escacabarossi, Francisca; Dias Pacobahyba, Lucilia (Journal of Interdisciplinary Debates, 2025)
Due to the pandemic caused by the novel coronavirus, the Pedagogical Residency Program (PRP) had to adapt to a new format called Emergency Remote Teaching (ERE). Teachers, accustomed to the face-to-face classroom, had to reinvent themselves to teach remote classes, experiencing new ways of teaching. And the residents, who participate in the program, also had to adapt to this scenario. The initiation into teaching, even during academic training, is of paramount importance for the future teacher, since it is a way to offer them other perspectives in relation to the school, in relation to their role in society as a shaper of citizens, and in relation to their future, acquiring rich experiences that contribute to the construction of their teaching identity. Given this context, the present project aims to report the experiences of an undergraduate student in Biological Sciences at the Federal University of Roraima (UFRR) as a participant in the Pedagogical Residency Program at the Application School of the Federal University of Roraima (CAp/UFRR), focusing on one of her main experiences during the program: addressing the topic of evolution with 3rd-year high school students for the first time, promoting reflection on this experience.